Erratum: Using A Tiered Approach for Implementing Networked Learning Communities: A Case Study on Developing the Capacity of Leaders to Implement Systemwide Innovations within International Training and Development Programs - JIAEE Editors (Journal of International Agricultural and Extension Education, 2024)
Correction: The DOI of the article "Anderson, J. C., Kaufman, E., Coartney, J., Mitra, S., & Cash, C. (2020). Using A Tiered Approach for Implementing Networked Learning Communities: A Case Study on Developing the Capacity of Leaders to Implement Systemwide Innovations within International Training and Development Programs. Journal of International Agricultural and Extension Education, 27(1), 6-14” was incorrect as published. The correct DOI is: 10.5191/iaee.2020.27101